Islamic Press Theory in Islamic Journalistic Ethics (Study of the Holy Qur'anic Verses as Guidelines for Peaceful Journalism) - Nadhiroh Nadhiroh; Mami Eva Novayani (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2022)
A This article examines the formulation of Islamic Press Theory in Islamic Journalistic Ethics. The rules in carrying out journalistic duties cannot be separated from Islamic teachings that are guided by the Koran. The scope of is limited to the study of the Holy Qur'anic verses that can be used as a guide for peace journalism. So far, some academics and members of the Muslim press have used western press theory in scientific studies and guidelines for carrying out journalistic duties. The purpose of this study is to examine the verses of the Holy Qur'an related to the principles of peace journalism. In addition, this study is expected to add insight into the guidelines for peace journalism that exist in Islam and can be applied in carrying out the duties of press personnel. The researcher uses a qualitative content analysis approach to examine some of the holy verses of the Koran related to Islamic journalistic ethics to be used as guidelines in journalism. peace. Researchers also use supporting documents from books, journals and internet sources. The results of the study indicate that the formulation of Islamic Press Theory needs to be continuously socialized in various activities, both lectures or journalistic training, especially on Islamic campuses. In the Qur'an there are several holy Qur'anic verses that can be used as guidelines in carrying out peace journalism. Some of the verses of the Koran are Al Hujurat [49]: 1-13 Al Ahzab [33]: 70 Al Nur [24]: 19.